Commutative Algebras of Toeplitz Operators on the Bergman Space - Nikolai L. Vasilevski ; edited by I. Gohberg, D. Alpay, J. Arazy, A. Atzmon, J. A. Ball, H. Bart, A. Ben-Artzi, H. Bercovici, A. Böttcher, K. Clancey, R. Curto, K. R. Davidson, M. Demuth, A. Dijksma, R. G. Douglas, R. Duduchava, A. Ferreira dos Santos, A. E. Frazho, P. A. Fuhrmann, B. Gramsch, H. G. Kaper, S. T. Kuroda, L. E. Lerer, B. Mityagin, V. Olshevski, M. Putinar, A. C. M. Ran, L. Rodman, J. Rovnyak, B. -W. Schulze, F. Speck, I. M. Spitkovsky, S. Treil, C. Tretter, H. Upmeier, N. Vasilevski, S. Verduyn Lunel, D. Voiculescu, D. Xia, D. Yafaev. (Springer, 2017)
436p.